Abatement technology and the environment-growth nexus with education - Xavier Pautrel (Fondazione Eni Enrico Mattei (FEEM), 2011)
This article challenges the conventional result that a tighter environmental tax has no long-run effect on human capital accumulation in the presence of pollution arising from final output production. It demonstrates that the technology used in the abatement sector determines the existence and the direction of the growth-effect. A tighter environmental tax rises (respectively reduces) human capital accumulation in the presence of pollution arising from final production, if the abatement sector is relatively more intensive in human (resp. physical) capital than final sector. That result always holds for finite lifetime but for infinite lifetime it only holds when labor supply is endogenous. The transitional impact of a tighter environmental policy is also investigated.
Keywords: Q5; Q58; 330; Growth; Environment; Overlapping Generations; Human Capital; Abatement